2015
DOI: 10.3109/14756366.2015.1018246
|View full text |Cite
|
Sign up to set email alerts
|

The slow dissociation rate of K-1602 contributes to the enhanced inhibitory activity of this novel alkyl–aryl-bearing fluoroketolide

Abstract: Ketolides belong to the latest generation of macrolides and are not only effective against macrolide susceptible bacterial strains but also against some macrolide resistant strains. Here we present data providing insights into the mechanism of action of K-1602, a novel alkyl-arylbearing fluoroketolide. According to our data, the K-1602 interacts with the ribosome as a onestep slow binding inhibitor, displaying an association rate constant equal to 0.28 Â 10 4 M À1 s À1and a dissociation rate constant equal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
1
0
4
Order By: Relevance
“…Moreover, while their association rate constants (k on ) are nearly identical, there are large differences in their dissociation rate constants (k off values). The k off values for some macrolides are extremely low, in the range of 10 À5 s À1 , indicating that these macrolides are almost irreversibly bound to the ribosome (Di Giambattista et al, 1987;Dinos and Kalpaxis, 2000;Dinos et al, 2003;Krokidis et al, 2016). Mankin and colleagues have suggested that such very low macrolide dissociation constants from the ribosome may also contribute to their bactericidal effect (Svetlov and Mankin, personal communication).…”
Section: Mode Of Actionmentioning
confidence: 99%
“…Moreover, while their association rate constants (k on ) are nearly identical, there are large differences in their dissociation rate constants (k off values). The k off values for some macrolides are extremely low, in the range of 10 À5 s À1 , indicating that these macrolides are almost irreversibly bound to the ribosome (Di Giambattista et al, 1987;Dinos and Kalpaxis, 2000;Dinos et al, 2003;Krokidis et al, 2016). Mankin and colleagues have suggested that such very low macrolide dissociation constants from the ribosome may also contribute to their bactericidal effect (Svetlov and Mankin, personal communication).…”
Section: Mode Of Actionmentioning
confidence: 99%
“…Кинетический анализ макролидов показал, что большинство из них действуют как медленно связывающиеся ингибиторы [50]. Кроме того, при практически идентичных значениях показателей константы скорости ассоциации (k on ) показатели константы скорости диссоциации (k off ) у разных макролидов в значительной степени отличаются между собой.…”
Section: механизм действия макролидовunclassified
“…Поскольку многие клинические проявления ТИН неспецифичны (электролитные нарушения, умеренная протеинурия, снижение СКФ), основным методом подтверждения диагноза является биопсия почки. Помимо оценки активности воспаления и выраженности тубулоинтерстициального фиброза морфологическое исследование ткани почки позволяет обнаружить патогномоничные для некоторых заболеваний особенности, в частности специфические паттерны фиброза и инфильтрацию IgG4-позитивными плазматическими клетками при IgG4-ассоциированном заболевании [47], отложение кристаллов моноурата натрия и умеренную выраженность воспалительной инфильтрации при уратной нефропатии [48], специфические гранулемы при саркоидозе [49], а сопутствующие признаки поражения сосудов и ТМА в биоптате могут указывать на наличие АФС [50].…”
Section: тубулоинтерстициальный нефритunclassified
“…Несмотря на иммуносупрессивную терапию, у части больных СКВ сохраняется воспалительная активность и/или наблюдаются обострения. В канадском исследовании стойкая ремиссия заболевания была достигнута только у 10% пациентов, в то время как у 9% -персистировала активность, а у 67% -развивались обострения СКВ [50]. В многоцентровом 2-летнем исследовании, проводившемся в нескольких странах Европы, обострения СКВ были зарегистрированы более чем у половины из 412 пациентов [51].…”
Section: перспективы стероидосберегающей терапииunclassified
See 1 more Smart Citation